CRISPR medicine for blood disorders: Progress and challenges in delivery - Mohammadian Gol, Tahereh; Ureña-Bailén, Guillermo; Hou, Yujuan; Sinn, Ralph; Antony, Justin S.; Handgretinger, Rupert; Mezger, Markus (Frontiers in Genome Editing, 2023)
Blood disorders are group of diseases including hematological neoplasms, clotting disorders and orphan immune deficiency diseases that affects human health. Current improvements in genome editing based therapeutics demonstrated preclinical and clinical proof to treat different blood disorders. Genome editing components such as Cas nucleases, guide RNAs and base editors are supplied in the form of either a plasmid, an mRNA, or a ribonucleoprotein complex. The major delivery vehicles for such components include viral vectors (e.g. AAVs and LVs), non-viral vectors (e.g. LNPs and polymers) and physical delivery methods (e.g. electroporation and microinjection). Each of the delivery vehicle specified above has its own advantages and disadvantages and development of a safe transferring method for ex vivo and in vivo application of genome editing components is still a big challenge. Moreover, the delivery of genome editing payload to the target blood cells possess key challenges to provide a possible cure for patients with inherited monogenic blood diseases and hematological neoplastic tumors. Here, we critically review and summarize the progress and challenges related to the delivery of genome editing elements to relevant blood cells in an ex vivo or in vivo setting. In addition, we have attempted to provide a future clinical perspective of genome editing to treat blood disorders with the possible clinical grade improvements in delivery methods.